2006
DOI: 10.4049/jimmunol.177.1.255
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of CD8+ T Cells in Advanced-Stage Tumors and Delay of Disease Progression following Secondary Immunization against an Immunorecessive Epitope

Abstract: Self-reactive T cells that survive the process of positive and negative selection during thymocyte development represent potential effector cells against tumors that express these same self-Ags. We have previously shown that CD8+ T lymphocytes (TCD8) specific for an immunorecessive epitope, designated epitope V, from the SV40 large T Ag (Tag) escape thymic deletion in line SV11 Tag-transgenic mice. In contrast, these mice are tolerant to the three most dominant Tag epitopes. The majority of the residual epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 69 publications
2
19
0
2
Order By: Relevance
“…Therefore, interfering with this checkpoint pathway boosts SDD-specific T CD8 , which in turn increases the epitope breadth of the overall T CD8 response to T Ag. This finding is important because SDDs are capable of conferring protective immunity in certain conditions (54, 55). They are ‘less visible’ to the immune system and may thus escape central or peripheral tolerance mechanisms in mice (56, 57) and humans (58).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interfering with this checkpoint pathway boosts SDD-specific T CD8 , which in turn increases the epitope breadth of the overall T CD8 response to T Ag. This finding is important because SDDs are capable of conferring protective immunity in certain conditions (54, 55). They are ‘less visible’ to the immune system and may thus escape central or peripheral tolerance mechanisms in mice (56, 57) and humans (58).…”
Section: Discussionmentioning
confidence: 99%
“…B6/T116A1 (B6/V-only Tag) cells express a Tag variant in which epitopes I (residues 207-215) and II/III (residues 223-231) are deleted and epitope IV is inactivated by alanine substitution of residues 406, 408, and 411, but in which epitope V remains intact (22) and were propagated in vitro as previously described (19). Ex vivo lymphocytes were maintained in complete RPMI 1640 medium supplemented with 10% fetal bovine serum (FBS), 100U/mL of penicillin, 100 μg/mL streptomycin, 2 mM L-glutamine, and 50 μM 2-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Adoptive transfers were performed as described previously (19) by intravenous injection of 5×10 6 clonotypic naïve TCR-V cells per mouse. For immunization, 5×10 7 B6/V-only Tag cells were injected intraperitoneally in 0.5 mL of PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccination with tumour-associated antigens (TAAs) has been reported to lead to expansion and accumulation of CD8 + CTLs within the tumour, resulting in enhancement of tumour regression. 21, 22 Previously, we have reported that virus-like particles (VLP) derived from rabbit haemorrhagic virus (RHDV) can be used as a vaccine construct to deliver TAAs to elicit a proliferative response of antigen-specific T cells and subsequent elimination of target cells in vivo . 23 In addition, we have also shown that TAA-expressing RHDV VLP were able to inhibit tumour growth in both a therapeutic and prophylactic manner.…”
mentioning
confidence: 99%